The microRNAs miR-204 and miR-211 maintain joint homeostasis and protect against osteoarthritis progression - Huang, Jian; Zhao, Lan; Fan, Yunshan; Liao, Lifan; Ma, Peter X.; Xiao, Guozhi; Chen, Di (Nature communications, 2019)
Osteoarthritis (OA) is a common, painful disease. Currently OA is incurable, and its etiology largely unknown, partly due to limited understanding of OA as a whole-joint disease. Here we report that two homologous microRNAs, miR-204 and miR-211 , maintain joint homeostasis to suppress OA pathogenesis. Specific knockout of miR-204/-211 in mesenchymal progenitor cells (MPCs) results in Runx2 accumulation in multi-type joint cells, causing whole-joint degeneration. Specifically, miR-204/-211 loss-of-function induces matrix-degrading proteases in articular chondrocytes and synoviocytes, stimulating articular cartilage destruction. Moreover, miR-204 / -211 ablation enhances NGF expression in a Runx2-dependent manner, and thus hyper-activates Akt signaling and MPC proliferation, underlying multiplex non-cartilaginous OA conditions including synovial hyperplasia, osteophyte outgrowth and subchondral sclerosis. Importantly, miR-204 /- 211 -deficiency-induced OA is largely rescued by Runx2 insufficiency, confirming the miR-204 /- 211- Runx2 axis. Further, intraarticular administration of miR-204 -expressing adeno-associated virus significantly decelerates OA progression. Collectively, miR-204 / -211 are essential in maintaining healthy homeostasis of mesenchymal joint cells to counteract OA pathogenesis. Osteoarthritis involves whole-joint tissue degeneration. Here, the authors show that miR-204 and miR-211 in mesenchymal joint cells regulate their proliferation, catabolic and osteogenic responses, and that disease progression is ameliorated by intra-articular miR-204 delivery in mice.